Impacto da principal aplicação informática utilizada nos processos de trabalho individual: aplicação numa autarquia local Portuguesa - Laureano, Raul M. S.; Bailoa, Sónia; Laureano, Luís (Proceedings TMS Int. Conference 2012: Tourism Management, Marketing, & ICT Management, 2013)
Town Council management must have a continuous focus on the satisfaction of the citizens and workers regarding the quality of services provided. The annual investments in technology should contribute to achieving those objectives. This study analyses the impact of the technology, in particular, of the most used computer applications in one Town Council on the daily work activities of its collaborators, as an evaluation proxy of the investment made. A questionnaire was distributed to the collaborators who work daily with the technologies in the Town Council and the 810 answers received show that the main computer applications used are Microsoft Office and SmartDocs. These applications have impact on the seven work dimensions analyzed, with the major impact being on the productivity level and the minor impact on innovation and on decision making. The impact level of each application on each dimension is diverse, and significant differences were found between Microsoft Office e SmartDocs regarding management control and information security.